The current state and problems of studying the biological effects of THz irradiation - E. A. Butikova; I. A. Razumov; O. V. Poveshchenko; V. V. Kanygin (Acta Biomedica Scientifica)
Background. Terahertz radiation (THz), which occupies the frequency range from 0.1 to 10 THz, has been a topic of limited research for a long time due to the difficulty in creating sources and detecting it. Recent advancements in semiconductor and nanotechnology, however, have led to the development of THz technologies in areas such as communications, medicine, and safety. Nevertheless, there are concerns about the potential health and environmental effects of these technologies.The aim. Summarize the current state of research in the fi of cellular eff ts arising from exposure to THz. Special attention is paid to the use of offi e technologies, in particular metabolomics, proteomics, transcriptomics to study the eff ts of THz on living systems. The review also aims to analyze key patterns of biological eff ts caused by THz and assess the prospects for further research and application of THz in biomedical and biotechnological direction and also features of the experiment organization by research infl   e of THz. To write the review, a search for scientifi publications was carried out using PubMed, Google Scholar, Scopus, IEEE Xplore sources for the period from 2000 to 2024.Discussion. THz studies have shown non-thermal effects on cells, including genotoxicity and changes in gene expression. However, the results vary depending on the study conditions and cell types used. Most of the research has been conducted in vitro on various cell lines, and the effects depend on radiation parameters such as wavelength and intensity. For epithelial cells and fibroblasts, the cytotoxicity is generally low at 1 THz, although genotoxic effects cannot be ruled out. THz has also been shown to reduce DNA methylation in tumor cells, which could be useful for diagnosis. Omics technologies are helping to study the molecular mechanisms underlying these effects, but standardizing methods is crucial to accurately differentiate between thermal and non-thermal mechanisms.Conclusion. The review emphasizes the importance of THz research and its impact on living systems. However, the available data is limited and dispersed. To comprehend the mechanisms of non-thermal effects, further detailed experimental investigations are required, including metabolomics approaches for analyzing biochemical responses to THz radiation.